Cost-effectiveness of implantable cardiac devices in patients with systolic heart failure. Issue 21 (13th July 2016) - Mealing, Stuart; Woods, Beth; Hawkins, Neil; Cowie, Martin R; Plummer, Christopher J; Abraham, William T; Beshai, John F; Klein, Helmut; Sculpher, Mark
Abstract : Objective: To evaluate the cost-effectiveness of implantable cardioverter defibrillators (ICDs), cardiac resynchronisation therapy pacemakers (CRT-Ps) and combination therapy (CRT-D) in patients with heart failure with reduced ejection fraction based on a range of clinical characteristics. Methods: Individual patient data from 13 randomised trials were used to inform a decision analytical model. A series of regression equations were used to predict baseline all-cause mortality, hospitalisation rates and health-related quality of life and device-related treatment effects. Clinical variables used in these equations were age, QRS duration, New York Heart Association (NYHA) class, ischaemic aetiology and left bundle branch block (LBBB). A UK National Health Service perspective and a lifetime time horizon were used. Benefits were expressed as quality-adjusted life-years (QALYs). Results were reported for 24 subgroups based on LBBB status, QRS duration and NYHA class. Results: At a threshold of £30 000 per QALY gained, CRT-D was cost-effective in 10 of the 24 subgroups including all LBBB morphology patients with NYHA I/II/III. ICD is cost-effective for all non-NYHA IV patients with QRS duration <120 ms and for NYHA I/II non-LBBB morphology patients with QRS duration between 120 ms and 149 ms. CRT-P was also cost-effective in all NYHA III/IV patients with QRS duration >120 ms. Device therapy is cost-effective in most patient groups with LBBB at a threshold of £20 000 per QALY gained. Results were robust to altering key model parameters. Conclusions: At a threshold of £30 000 per QALY gained, CRT-D is cost-effective in a far wider group than previously recommended in the UK. In some subgroups ICD and CRT-P remain the cost-effective choice.